Examining the Influence of Gender Equity Initiatives on STEM Student Demographics - Lara-Prieto, Vianney; Rodríguez-Rosales, Adriana; Martinez-Torteya, Carlos Eduardo; Ruiz-Cantisani, M. Ileana; Huesca, Gilberto; Acevedo, Joaquín (LACCEI, 2024)
Globally, men continue to outnumber women three-to-one in Science, Technology, Engineering and Mathematics (STEM), a trend evident in much of Latin America, including Mexico. Over the past decade, numerous global initiatives have sought to raise awareness about the gender gap in STEM fields and foster the active participation and development of women. Our institution, with a particular focus on the School of Engineering and Sciences, has committed to advancing gender equity. The different initiatives undertaken are presented in chronological order, outlining the institution ́s journey in this regard. The objective of this work is to explore the influence of the multiple gender equity initiatives implemented in recent years at our institution on the demographics of STEM students. The study includes both freshmen and graduates from the 18 university programs offered by the School of Engineering and Sciences over the past four years. While the results may not fully meet expectations in terms of achieving proportional representation for women, significant progress has been made in cultivating an institutional culture of equity and inclusion. Each individual effort contributes to this transformation and encourages reflection on a personal level, fostering a sense of responsibility to become ambassadors for women ́s empowerment. These efforts should continue, further strengthening and inclusive culture within the university and extending their influence to the broader community. This collective commitment is essential for achieving gender equality in STEM fields.